Novel branched polyampholytes and polyplexes for gene delivery: Synthesis, structure and efficient transfection - Mitina, Nataliya; Finiuk, Nataliya; Izhyk, Oleh; Garamus, Vasil M.; Harhay, Khrystyna; Bulkurcuoglu, Buenyamin; Ceylan, Sebnem Ercelen (Elsevier, 2025)
The presented study is aimed at the synthesis of novel branched polyampholytes with precisely controlled architectures, structures, and colloidal-chemical properties as well as their complexes with plasmid DNA as nonviral vectors to advance the field of gene delivery. The relationships between polymer synthesis, architecture, colloidal characteristics, polyplex size and morphology, and transfection efficiency was of an interest for this study also. This research is crucial for addressing the challenges associated with gene therapy and unlocking the full potential of these branched polyampholytes. The main achievements: The method of synthesis of the polyampholytes combining anionic backbone and grafted cationic poly(DMAEMA) chains via low temperature controlled radical polymerization (CRP) initiated by multisite oligoperoxide metal complex (OMC) in organic media was developed. The dependences of the CRP kinetic parameters of the obtaining the polyampholyte of desired architecture, structural and colloidal-chemical characteristics upon media polarities were established. The relations between the synthesis of polyampholytes defining grafting degree, lengths of side cationic chains, colloidal-chemical characteristics, and morphology of polyplexes formed with plasmid DNA as well as transfection efficiency were established. Conclusions: Kinetic peculiarities of the CRP of DMAEMA initiated by multi-site oligoperoxide complex in polar organic media influenced the architecture, fine structure and colloidal-chemical properties of the branched polyampholytes. These unique polymeric surfactants complexed with DNA formed polyplexes with varying sizes, charges and morphologies. Our findings demonstrate that these properties are pivotal in determining transfection efficiency.
Keywords: Controlled radical polymerization; Branched polyampholytes; Polymer architecture; Polyplexes; Morphology; In vitro transfection; Transfection efficiency